The law of freedom the Supreme Court and democracy - Eisler, Jacob 1982- (Cambridge University Press, 2023)
The Supreme Court has been at the center of great upheavals in American democracy across the last seventy years. From the end of Jim Crow to the rise of wealth-dominated national campaigns, the Court has battled over if democracy is an egalitarian collaboration to serve the good of all citizens, or a competitive struggle by private interests. In The Law of Freedom, Jacob Eisler questions why the Court has the moral authority to shape democracy at all. Analyzing leading cases through the lens of philosophy and social science, Eisler demonstrates how the soul of election law is a battle between two philosophical understandings of democratic freedom and popular self-rule. This remarkable book reveals that the Court's battle over democracy has shaped how Americans rule themselves, marking election law as the most dramatic judicial intervention in constitutional history